Uji Stabilitas Sensor DT-Sense Color Untuk Mendeteksi Warna dan Sensor MQ137 Untuk Mendeteksi Gas Ammonia Berbasis Mikrokontroler - Fereddy Yulianus Napitupulu; Fauziyah Fauziyah; Heron Surbakti (Faculty of Mathtmatics and Natural Sciences, 2019)
This study has conduct with origami color paper and ammonia gas to test the stability that serves to DT-Sense color sensors and MQ137 ammonia gas sensors. Method of this study is experimental laboratory scale. DT-Sense color sensor placed on material origami color paper test and measurement of three repetitions and then compared the results obtained against the database default provisions. The results of the RGB color by using origami color paper compared with the data base color like a hot pink, black, yellow, red, orange, green liner, royal blue, dark green and brown saddle with stability range digital tools 0-255 number. Measurement of liquid ammonia evaporation with a content of 25% with a different sample preparation. Measurements were performed for 250 seconds (s). Based on the observations of the ammonia concentration value detected by the sensor MQ137 related with the sensor voltage which is R = 0.9996 and stability of concentration of ammonia and ADC values have a related with R = 1. Based on observations sensr MQ137 which has been designed only able to detection of ammonia concentration of +/- 1300 ppm and MQ137 sensor voltage with +/- 5 volts.